On the Relationship between the Inhomogeneous Wave and Helmholtz Equations in a Fractional Setting - Mateo Dulce; Alexander Getmanenko (Abstract and Applied Analysis)
We study convergence of solutions of a space and time inhomogeneous fractional wave equation on the quarter-plane to the stationary regime described by solutions of the Helmholtz equation.